The causal effect of multitasking on work-related mental health: The more you do, the worse you feel - Anna Katharina Pikos (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper analyses whether there is a causal relationship between work-related mental health problems and multitasking, the number of tasks performed at work. The data comes from two cross sectional surveys on the German working population. The empirical strategies uses technological change as an instrument for multitasking. In the first stage, the introduction of new production and information technologies is associated with increases in multitasking. Production technology adoption has larger associations to manual multitasking and informational technology adoption to cognitive multitasking. There is evidence for a causal effect of multitasking on emotional strain, emotional exhaustion and burnout.
Keywords: I10; J28; 330; work-related mental health; multitasking; job satisfaction